The ErbB Signaling Network and Its Potential Role in Endometrial Cancer - Georgios Androutsopoulos; Ioanna Styliara; Evgenia Zarogianni; Nadia Lazurko; George Valasoulis; Georgios Michail; Georgios Adonakis (Epigenomes, 2023)
Endometrial cancer (EC) is the second most common malignancy of the female reproductive system worldwide. The updated EC classification emphasizes the significant role of various signaling pathways such as PIK3CA-PIK3R1-PTEN and RTK/RAS/β-catenin in EC pathogenesis. Some of these pathways are part of the EGF system signaling network, which becomes hyperactivated by various mechanisms and participates in cancer pathogenesis. In EC, the expression of ErbB receptors is significantly different, compared with the premenopausal and postmenopausal endometrium, mainly because of the increased transcriptional activity of ErbB encoding genes in EC cells. Moreover, there are some differences in ErbB-2 receptor profile among EC subgroups that could be explained by the alterations in pathophysiology and clinical behavior of various EC histologic subtypes. The fact that ErbB-2 receptor expression is more common in aggressive EC histologic subtypes (papillary serous and clear cell) could indicate a future role of ErbB-targeted therapies in well-defined EC subgroups with overexpression of ErbB receptors.